A molecular-properties-based approach to understanding PDZ domain proteins and PDZ ligands - Giallourakis, Cosmas; Cao, Zhifang; Green, Todd; Wachtel, Heather; Xie, Xiaohui; Lopez-Illasaca, Marco; Daly, Mark; Rioux, John; Xavier, Ramnik (Genome Research, 2006)
PDZ domain-containing proteins and their interaction partners are mutated in numerous human diseases and function in complexes regulating epithelial polarity, ion channels, cochlear hair cell development, vesicular sorting, and neuronal synaptic communication. Among several properties of a collection of documented PDZ domain–ligand interactions, we discovered embedded in a large-scale expression data set the existence of a significant level of co-regulation between PDZ domain-encoding genes and these ligands. From this observation, we show how integration of expression data, a comparative genomics catalog of 899 mammalian genes with conserved PDZ-binding motifs, phylogenetic analysis, and literature mining can be utilized to infer PDZ complexes. Using molecular studies we map novel interaction partners for the PDZ proteins DLG1 and CARD11. These results provide insight into the diverse roles of PDZ–ligand complexes in cellular signaling and provide a computational framework for the genome-wide evaluation of PDZ complexes.
10.1101/gr.5285206